Electrical Stimulation for Immune Modulation in Cancer Treatments - Das, Ritopa; Langou, Sofia; Le, Thinh T.; Prasad, Pooja; Lin, Feng; Nguyen, Thanh D. (Frontiers in Bioengineering and Biotechnology, 2022)
Immunotherapy is becoming a very common treatment for cancer, using approaches like checkpoint inhibition, T cell transfer therapy, monoclonal antibodies and cancer vaccination. However, these approaches involve high doses of immune therapeutics with problematic side effects. A promising approach to reducing the dose of immunotherapeutic agents given to a cancer patient is to combine it with electrical stimulation, which can act in two ways; it can either modulate the immune system to produce these immune cytokines and agents in the patient’s body or it can increase the cellular uptake of these immune agents via electroporation. Electrical stimulation in form of direct current has been shown to reduce tumor sizes in immune-competent mice while having no effect on tumor sizes in immune-deficient mice. Several studies have used nano-pulsed electrical stimulations to activate the immune system and drive it against tumor cells. This approach has been utilized for different types of cancers, like fibrosarcoma, hepatocellular carcinoma, human papillomavirus etc. Another common approach is to combine electrochemotherapy with immune modulation, either by inducing immunogenic cell death or injecting immunostimulants that increase the effectiveness of the treatments. Several therapies utilize electroporation to deliver immunostimulants (like genes encoded with cytokine producing sequences, cancer specific antigens or fragments of anti-tumor toxins) more effectively. Lastly, electrical stimulation of the vagus nerve can trigger production and activation of anti-tumor immune cells and immune reactions. Hence, the use of electrical stimulation to modulate the immune system in different ways can be a promising approach to treat cancer.